Improvement of Animal Classification Materials Learning Result with Audio Visual Media in Class V Students - Norma Affiani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research was to improve student learning outcomes in science grade V  elementary schools with a zoom meeting assisted audio-visual media. The research conducted was a Classroom Action Research (PTK) with three cycles. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting was conducted with a post test to determine the development of students. The condition of student learning completeness before there is action is 32%. In the first cycle the students who completed after carrying out the post test were 52%. In the second cycle students who completed after carrying out the post test were 72%. In cycle III the students who completed after carrying out the post test were 100%. These results indicate that the use of audio-visual media can improve student learning outcomes, especially grade V science at SDN Kowangan.